1979
DOI: 10.1097/00006842-197910000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Risk Factors in the Developmental of Infectious Mononucleosis*

Abstract: In a 4-year prospective seroepidemiological study of infectious mononucleosis (IM) of one class of some 1400 cadets at the West Point Military Academy, sugceptibles and immunes were identified by the absence or presence of antibody to Epstein-Barr virus (EBV), the causative agent, and new infections by the appearance of antibody (seroconversion). On entry, about Va lacked EBV antibody, of whom some 20% became infected (seroconverted); about Vi of seroconverters developed definite, clinical and recognized IM. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(62 citation statements)
references
References 20 publications
1
60
0
1
Order By: Relevance
“…For example, psychological stress has been linked to the development and severity of EBV-associated infectious mononucleosis (32). Animal studies have also demonstrated the impact of stress on the virus-specific primary and memory immune responses to HSV-1 in mice (33).…”
Section: Discussionmentioning
confidence: 99%
“…For example, psychological stress has been linked to the development and severity of EBV-associated infectious mononucleosis (32). Animal studies have also demonstrated the impact of stress on the virus-specific primary and memory immune responses to HSV-1 in mice (33).…”
Section: Discussionmentioning
confidence: 99%
“…An early study followed 437 seronegative West Point cadets through four years of intensive schooling to determine which factors contributed to their developing mononucleosis (68). Risk factors included having an overachiever father, high measures of self-motivation, and poor academic performance.…”
Section: Functional/response Assaysmentioning
confidence: 99%
“…Stress may also affect primary infection with a herpesvirus (35). Fourteen hundred West Point cadets who were seronegative for Epstein-Barr virus at the start of the study were followed prospectively for 4 years.…”
Section: Stress and Resistance To Infectious Diseasesmentioning
confidence: 99%